Rancang Bangun Mesin Uji Universal Untuk Pengujian Tarik dan Tekuk Bertenaga Hidrolik - Nanang Ali Sutisna (President University, 2021)
Universal Testing Machine or UTM (Universal Testing Machine) is a material testing machine that has more than one type of material testing. The purpose of this research is to design and analyze the strength of the UTM construction for tensile and bending tests. This machine uses a hydraulic jack as a power source to provide the required load. The design is limited to a load of 1.4 tons while the maximum construction load is 5 tons according to the hydraulic jack capacity. The method used in this study begins with a design using CAD and then analyzed with the finite element method. From the results of the analysis and evaluation, the designed tool can be used safely in accordance with the specifications used. The results showed that from the experimental results on the tensile and bending test specimens, both tests were successfully carried out. The tensile test was carried out with SUS 304 and SS400 with different thicknesses with dimensions according to ASTM E8 standards, while the bending test was carried out on ASTM A36 material with a size of 200 x 40 x 6 mm. After the test is carried out, the construction of the machine is checked for possible defects due to the test, namely the upper and lower clamps, punches and dies, and the engine frame. As a conclusion, after testing, it turns out that no damage or defects were found in all the parts examined